Potent Acid Suppression With Vonoprazan vs Proton Pump Inhibitors Does Not Have Higher Association With Clostridioides difficile Infection. (13th August 2021) - Watanabe, Kenta; Shimodaira, Yosuke; Takahashi, So; Fukuda, Sho; Koizumi, Shigeto; Matsuhashi, Tamotsu; Iijima, Katsunori
Abstract : INTRODUCTION: Proton pump inhibitors (PPIs) are associated with the onset of Clostridioides difficile infection (CDI). Although a new potassium-competitive acid blocker, vonoprazan, consistently shows a more potent acid inhibitory effect in comparison to PPIs, the risk of CDI in vonoprazan-treated patients relative to those treated with PPIs is unknown. In this retrospective case-control study, using a nationwide hospital-based administrative database in Japan, we investigated the association of the onset of CDI in patients treated with vonoprazan. METHODS: A CDI case was defined as a case in which a patient was diagnosed and treated for CDI. For each CDI case, 3 non-CDI patients were extracted as controls. Information on the usage of acid suppressants in the 2 months before the onset of CDI and other confounding factors was collected. Relative associations of gastric acid suppressants with the onset of CDI were estimated. RESULTS: A total of 4, 466 CDI cases and 13, 220 of non-CDI controls were extracted. A multivariate conditional regression analysis revealed that PPI or vonoprazan use was modestly, but significantly associated with CDI (odds ratio [95% confidence interval]: PPI, 1.3 [1.2–1.4]; vonoprazan, 1.4 [1.2–1.7]). With PPI users as a reference, vonoprazan did not show a stronger association with CDI (odds ratio [95% confidence interval]: 1.07 [0.91–1.26]). DISCUSSION: We found a significant positive association between vonoprazan use and CDI; however, the magnitude of the association was not beyond that in PPI users. This is the first report on any potential adverse effects of vonoprazan.